2020
DOI: 10.1186/s12939-020-01238-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of social network diversity in the disablement process: a comparison of causal inference methods and an outcome-wide approach to the Indonesian Family Life Surveys, 2007–2015

Abstract: Background: Social networks (SN) have been proven to be instrumental for healthy aging and function as important safety nets, particular for older adults in low and middle-income countries (LMICs). Despite the importance of interpreting health outcomes in terms of SN, in many LMICsincluding Indonesiaepidemiological studies and policy responses on the health effects of SN for aging populations are still uncommon. Using outcome-wide multi-method approaches to longitudinal panel data, this study aims to outline m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 119 publications
(174 reference statements)
0
6
0
Order By: Relevance
“…To the best of our knowledge, our study is one of the first to incorporate how precarity and loneliness interrelate in the lifeworld of OACs in a transitioning LMIC context. The pathways through which social networks may exacerbate precarious aging trajectories and negatively impact health and wellbeing among aging Indonesian populations have been explored in our previous work on the health effects of social network diversity ( Schröders et al, 2020 ) and the role of network dynamics on healthcare utilization outcomes ( Schröders et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…To the best of our knowledge, our study is one of the first to incorporate how precarity and loneliness interrelate in the lifeworld of OACs in a transitioning LMIC context. The pathways through which social networks may exacerbate precarious aging trajectories and negatively impact health and wellbeing among aging Indonesian populations have been explored in our previous work on the health effects of social network diversity ( Schröders et al, 2020 ) and the role of network dynamics on healthcare utilization outcomes ( Schröders et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…For selecting study areas below regional level, we used socioeconomic development together with the concepts of rurality/ urbanity. Based on the notion that in LMICs in general (Perkins et al, 2015) and in Indonesia in particular (Schröders et al, 2020) the presence or absence of social networks make a pronounced difference to the ultimate consequences of poverty on people's lives, we decided to purposively sample two regencies which vary significantly with regards to their poverty levels and human development indices (HDI): the Sleman regency ranking best within the region with a poverty rate of 8.21% and a HDI of 82.15; and the Gunung Kidul regency ranking last with 19.34% of its population being classified as poor and a HDI of 67.82 [Badan Pusat Statistik (BPS) D. I. Yogyakarta (Statistic Office of the Yogyakarta Special Region), 2018]. Many studies have shown that poverty in Indonesia is strongly related to the socio-cultural tendency of poor people to share their limited assets-a practice that makes people poorer as their social networks expand (Geertz, 1963;Alexander and Alexander, 1982).…”
Section: Sampling and Study Setting: Rural Gunung Kidulmentioning
confidence: 99%
See 2 more Smart Citations
“…Such 'fourth sector' service delivery [15] involves informal neighbouring and time giving on a one-to-one basis in recognition of an 'unmet need' at grassroots level, on the ground. These informal neighborhood community-based services and activities that rely upon localized networks are part of the fabric of rural community life [16], and include a diverse range of activities such as befriending and home visiting by members of church groups, social activities at village halls, informal gatherings and social contact that occurs while accessing services at village post offices or when visiting village pubs [14].…”
Section: Introductionmentioning
confidence: 99%